The relationship between coping mechanisms and level of hypertension Cot Masam village, Kuta Baro sub-district, Aceh besar district - Putra, Yadi; Mansuriza, Mansuriza; Karmila, Syifa (Jurnal EduHealth, 2024)
Hypertension is a condition where systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg. An unhealthy lifestyle is one of the causes of increasing blood pressure so that a coping mechanism is needed. This study aims to determine the relationship of coping mechanisms with the level of hypertension in Cot Masam village, Kuta Baro District, Aceh Besar. This study uses a descriptive correlative design that uses a cross sectional approach. The sample in this study was the Cot Masam community who experienced hypertension as many as 59 respondents. The sampling technique in this study was total sampling. The instruments used in this study used questionnaire sheets, sphygmomanometer and stestoscope. The results showed that the distribution of adaptive coping mechanisms was 16 respondents (48.5) with stage II hypertension. While out of 26 respondents with maladaptive coping mechanisms, 13 respondents (50.0%) were in prehypertension. The p-value is 0.012. This means that the p-value is < α = 0.05. So it can be stated that there is a relationship between coping mechanisms and the level of hypertension in Cot Masam village, Kuta Baro District, Aceh Besar Regency. Conclusions based on research that has been carried out 01-07 March 2023 in Cot Masam can be concluded that hypertension is in stage II and coping is maladaptive. Researchers suggest to respondents to approach coping mechanisms in lowering blood pressure experienced.